Tensão continua no oeste: história e representações da disputa de terra em Sede Trentin/Toldo Chimbangue nas páginas de O Estado (1982-1985) - Rocha, Douglas Satirio da (2016)
In the 1980s the land problems in the Western Santa Catarina region were highlighted in the newspapers of Santa Catarina State. Notes, news and reports contemplated the rising and the action of many social movements linked to land issues, marking a period where the region became represented as a space of constant "conflicts". In this scenario, highlights the process of taking back the Toldo Chimbangue’s land by the Kaingang indians in the early 1980s, in Chapecó-SC. The mobilization of indians faced great resistance from local farmer’s families, who lived in the required land, triggering a series of disputes widely monitored and reported in the press. Among the newspapers that reported the events involving this process, stands out in this period, the jornalistic coverage made by the newspaper “O Estado” – statewide newspaper, based in Florianópolis – SC. More than facts and informations, speeches and representations about a region historically known for land issues circulated throught the pages of the newspaper. This research analyzes the news published by the newspaper “O Estado” between 1982 and 1985 and aims to discuss the representations built on the process of competition for land between Indians and local farmers in Sede Trentin/Toldo Chimbangue. In a specifically way, this research seeks to identify which places were intended for this issue in the newspaper editions, examine how the newspaper ran the speeches of groups/instutions in "defense" and/or "accusation" of involveds, analyze how the narrative was articulated thought the diferents voices of indians and small farmers inside the same space being disputed, discuss the representations among the question and the individuals envolved, therefore, about the Western region. Following this goals, will be in evidence the comprehension of how the newspaper, in the process of reading, interpretation and representation of the reality, built certain senses and images of the facts that happened at the Sede Trentin/Toldo Chimbangue place.